Strategi Guru Pendidikan Agama Islam Dan Budi Pekerti Dalam Membentuk Keaktifan Belajar Dan Sikap Toleransi Siswa Kelas Inklusi Di SD Alam Mahira Bengkulu - Afrilia Dwi Cahya; Asiyah Asiyah (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
The research subjects were Islamic Religious Education and Character teachers, school principals, accompanying teachers, and students. The results of the research show that adapting learning materials, using inclusive learning methods, creating a conducive learning environment, fair and comprehensive assessment, involving both regular students and those with special needs in carrying out learning tasks, forms students' willingness to ask questions and participate in solving problems. in class, able to form active learning in inclusive classes. Then respect for differences, cooperation in heterogeneous groups, peaceful resolution of conflicts can form attitudes and tolerance in students in inclusive classes without discrimination. And the supporting factors at SD Alam Mahira Bengkulua are collaboration between PAI and Budi Pekerti teachers, accompanying teachers and parents, holding teacher professional development and training, as well as the existence of school policies that support inclusive education, while the inhibiting factors are limitations. learning media, the shortage of teachers with a Special Education (PLB) background, the striking difference in academic abilities between regular students and students with special needs, as well as the boredom often experienced by students with special needs which can disrupt class order and comfort.